Prawne warunki stabilizacji zatrudnienia kierownika zakładu pracy - Niedbała, Zdzisław (Wydział Prawa i Administracji UAM, 1988)
In conditions of the economic reform that is in conditions of self-dependence and self-government of enterprises, a special role is to be played by managerial staff. Among them the most important place is reserved for managers of state enterprises and cooperatives. The Labour Code provisions (Art. 4 and 23) declare that managers of enterprises represent the enterprises to their crews and manage those enteprises according to the principle of one-person rule The laws regulating the activity of state enteprises grant their managers the right to taking self-dependent lawful decisions. Carrying out such important tasks and competences requires high professional qualifications and organizational skills. At the same time, however, a condition of the efficient realization of those tasks is to guarantee to the managerial staff at least some basic conditions of employment stability. To a considerable degree the latter postulate has been implemented by the Act of Sept. 25, 1981 on State Enterprises. The provisions of the Act vest tasks of protecting the stability of employment of a manager in so-called founding organs, i.e. the State administration organs and the employees' councils of enterprises. So far, however, managers themselves have had no autonomous legal means to question the decisions recalling them from managerial posts. Similarly, members of the management of a cooperative may be recalled by a statutory organ of a cooperative without any reasons, i.e. without the recalling organ's duty to state the motives of dismissal. The proposals of changes in that respect in conditions of a new economic situation seem indispensable.
Legal conditions of stabilization of employment of a factory manager